The role of fiscal rules and institutions in shaping budgetary outcomes : Proceedings from the ECFIN Workshop held in Brussels on 24 November 2006 - Proceedings from the ECFIN Workshop 2006 : Brussels, Belgum); Deroose, Servaas; Ayuso-i-Casals, Joaquim; Flores, Elena; Moulin, Laurent; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
The Workshop "The role of fiscal rules and institutions in shaping budgetary outcomes" organized by the Directorate-General for Economic and Financial affairs of the European Commission on 24 November 2006 in Brussels aimed at enriching the debate on the fiscal arrangements and improving the understanding of their functioning. This Economic Paper contains all the paper presented in this event that was organised in four sessions. A first set of papers mainly focus on the impact of numerical fiscal rules on budgetary outturns. Other paper deal primarily with the appropriate design of fiscal rules and institutions. An additional group of papers addresses the relationship between the fiscal governance approach adopted by the EU Member States and their institutional and political frameworks. Finally the remaining presentations relate more directly to policy experiences.
Economic Papers